대용량 풍력발전 시스템의 계통연계기술에 관한 연구 - 정해광 (The Graduate School, Ajou University, 2014)
This thesis presents the grid-connection technique for a huge-capacity wind power system. The various studies are included for the design of a huge-capacity wind power system. Especially, the design of the power conditioning system (PCS) and the grid-connected filter which handle the high power can cause problems. To deal with the high power, many multi-level and parallel topologies were developed for the realization of the PCS and a LCL filter is adopted for the design of the grid-connected filter. However, a circulating current caused by the parallel converter topology and a resonance of the LCL filter can be critical problems to the wind power system. Moreover, a low voltage ride through (LVRT) requirement of the grid-code is essential considerations for a huge-capacity wind power system. This thesis proposes a development of the parallel converter topology and an optimal design of LCL filter. The converter is designed by the three-parallel topology to distribute the high-currents effectively. In addition, the optimal design of the sharing reactor is presented to reduce the circulating current. And the optimal design of the inverter side inductor which is the base of the LCL filter design is proposed. The proposed design method analyzes the current ripple of the two-level inverter to operate by the space vector modulation (SVM) method. According to the result of this analysis, the optimal inductance can be designed. The proposed wind power system which includes the parallel converter and LCL filter has some problems such as circulating current and resonance. To solve these problems, this thesis presents the compensator based on a PQR power theory. A PQR power theory which can control the harmonics and reactive power is used for the active power filter. In this thesis, the compensator reduces the distortion caused by resonance and circulating current. Finally, the control method to meet the LVRT requirement is presented. The proposed LVRT method includes an improved method for detecting grid faults, the design and control method of the dynamic braking resistor (DBR) circuit, and the control strategy for the system operations. The simulation model of 2.5MW wind power system is developed to verify the validity of the proposed wind power system. The performance of the LCL filter, PQR compensator, and LVRT control method are verified using this simulation model. The 10KW wind power simulator is also made, and its operation results show the superiority of the proposed wind power system.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2014. 2